2018
DOI: 10.1088/1361-6595/aac618
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of plasma dynamics and spatially varying O and OH concentrations in atmospheric pressure plasma jets impinging on glass, water and metal substrates

Abstract: Atmospheric pressure plasma jets (APPJs) have attracted considerable attention over the last decade, specifically for use in surface engineering. A comparative study of an APPJ, driven by pulsed DC voltage, is conducted in order to examine the plasma impingement onto different surfaces. In this paper, the effect of gas flow rate and composition is investigated using three kinds of substrates: dielectric glass, distilled water and metal plate using fast imaging. Alongside discharges associated with rising and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 40 publications
7
60
0
Order By: Relevance
“…The same macroscopic behaviors reported in Norberg et al [27] have been observed and their effect on the electron properties have been reported, with electron density close to the target reaching three times higher values with a metallic target than a glass target. Other experimental and numerical works [12,39,51] have found the same tendencies as in Norberg et al [27], in terms of influence of the target on discharge velocity, radial spreading on the target and electric field in the front of propagation.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…The same macroscopic behaviors reported in Norberg et al [27] have been observed and their effect on the electron properties have been reported, with electron density close to the target reaching three times higher values with a metallic target than a glass target. Other experimental and numerical works [12,39,51] have found the same tendencies as in Norberg et al [27], in terms of influence of the target on discharge velocity, radial spreading on the target and electric field in the front of propagation.…”
Section: Introductionsupporting
confidence: 71%
“…The interaction of jets with dielectric surfaces of different permittivities has been addressed in several experimental and numerical works [2,5,10,12,15,20,26,27,33,39,45,50,51,53]. In Norberg et al [27] it has been studied numerically in 2D the impact of He jets on dielectric and metallic grounded targets with a −15 kV voltage pulse.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the speed of the ionization wave and the electron/ion densities increase in the presence of such targets as compared to dielectrics with low permittivity [11]. On the contrary, a greater spread of the ionization wave on the surface and a deeper penetration of the electric field was observed for dielectric substrates [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 96%
“…Until now, some efforts have been made to investigate the interactions between APPJ and substrates from different perspectives . Viegas et al reported the volume and surface charge influence on the electric field distribution with numerical and experimental methods.…”
Section: Introductionmentioning
confidence: 99%
“…Viegas et al reported the volume and surface charge influence on the electric field distribution with numerical and experimental methods. Yue et al investigated the plasma dynamics and spatially varying O and OH concentrations with different substrates. Darny et al studied the effect of a conductive target on plasma properties in He discharge and identified the mechanisms after ionization front impact on the target surface.…”
Section: Introductionmentioning
confidence: 99%